Análisis espectral de la velocidad del viento cerca de la superficie y posibles fuentes de predictibilidad en la Península Ibérica - Utrabo-Carazo, Eduardo; Azorín-Molina, César; Aguilar, Enric; Brunet, Manola (Ministerio para la Transición Ecológica (España), 2022)
[EN]: This study analyzes in the frequency domain observed time series of mean nearsurface wind speed and daily peak wind gusts over the Iberian Peninsula. The main objective will be to explore possible sources of predictability in the medium-long term for these variables in the region. The spectral power density is estimated from the multitaper method, the spectrum shows that the behaviour is chaotic for periodsshorter than one year and quasi-periodic for periods longer than two years, which justifies the possibility of finding sources of predictability. Furthermore, the continuous wavelet transform allows us to determine non-stationary behaviour in the analyzed series, locating the most important oscillations in time. Finally, wavelet coherence will be calculated between both wind variables and various modes of ocean-atmosphere variability that may be related to wind speed in the region, such as: El Niño-Southern Oscillation, North Atlantic Oscillation, Western Mediterranean Oscillation or, the stratospheric polar vortex due to the influence of stratospheric sudden warmings in the peninsular troposphere. The main result is the high statistically significant correlation between wind variables and the polar vortex for periods close to the year with a time lag of about 2-3 months with respect to the antiphase, i.e., a negative correlation in which the polar vortex modulates the wind speed in the region with such a lag. This work may have direct applications in areas such as: wind power generation, agriculture, air quality, insurance and fishing industries, among others. [ES]: Este estudio analiza en el dominio de la frecuencia series temporales observadas de la velocidad media del viento cerca de la superficie y de las rachas máximas diarias en la Península Ibérica. El objetivo principal será explorar posibles fuentes de predictibilidad a medio-largo plazo para estas variables en la región. La densidad espectral de potencia se estima a partir del método multitaper obteniendo que el comportamiento es caótico ...